Artificial intelligence and critical thinking: a case study with educational chatbots - Brazão, Paulo; Tinoca, Luís (Frontiers in Education, 2025)
This article presents a qualitative investigation into the evolution of critical questioning that occurred in dialogic relationships between artificial intelligence (AI) and a group of higher education students. Drawing from students' class records, it attempts to understand the development of critical thinking within formal educational contexts, utilizing a five-level questioning framework: General and Defining, Specific, Applied, Integrative, and Critical Engagement. The results indicate the presence of questioning patterns centered on levels four and five—namely, the use of Integrative and Critical Engagement questions—emerging from contextualized discussions. Students' interactions with AI enabled them to observe: the diversity of questioning levels, the progression of critical thinking, areas for improvement within each working group, the encouragement of reflexivity and metacognition, engagement with complex concepts, visualization of practical concept applications, and the expansion of interdisciplinary thinking. This study contributes to the literature on education and technology by offering insights into how to structure effective dialogic interactions between students and AI systems.